Theatrical Terms in N. Humeniuk’s Novel “Heather Honey”: Linguo-stylistic Analysis (Linguostylistic Studies, 2022)
This article highlights the issue of theatrical terminology functioning features in N. Humeniuk’s novel “Heather Honey”. The author substantiates the idea that using specific concepts’ nominations in artistic language leads to their determinization. Terms in an artistic text are qualitatively different compared to a scientific text. At the same time, they are perceived in a different way than other lexical units of a work of art since they retain the “imprint” of a scientific style. Linguistic and stylistic analysis of the novel has revealed that the creative idea and, accordingly, the ideological and thematic content of the work are the factors that determine the use of theatrical terms. The presence of these nominations in the novel testifies to the writer's desire to describe more realistically the theatrical environment of the 20s-30s of the last century. The study has identified theatrical terms in the author's descriptions and in the characters' speech. The lexemes denoting theatrical concepts are used in some definite fragments of the novel compactly.The main function of terms in the novel is identification or, in other words, theatrical vocabulary firstly evokes an association with that sphere of cultural life from which it is drawn. Terms in the text also perform a signaling function – they are related to the plot line dealing with the relationships and professional activities of the actors. Theatrical terms are an integral part of the artistic image’s structure and serve to characterize the characters, their occupations/professions, and preferences. The writer does not provide any definitions of terms but yet emphasizes their belonging to another sphere by using several nominations of theatrical concepts in one sentence or in close contexts and involving specific theatrical phraseology. The term lexemes in the novel comprise the names of the dramatic work kinds, the forms of their stage embodiment, the names of actors, and the creative workers of the theater. A separate group of lexemes involves the words related to the audience.In the novel under analysis, theatrical terms are sometimes a part of the vivid, individual-author metaphors and comparisons, however, the associations, on the basis of which metaphorical images arise, are often related to the meaning of the term.
Keywords: stylistic coloring; determinologization; special concepts; artistic text; imagery